Intracerebral Distribution of the Oncometabolite d-2-Hydroxyglutarate in Mice Bearing Mutant Isocitrate Dehydrogenase Brain Tumors: Implications for Tumorigenesis - Pickard, Amanda J.; Sohn, Albert S. W.; Bartenstein, Thomas F.; He, Shan; Zhang, Yi; Gallo, James M. (Frontiers in Oncology, 2016)
The prevalence of mutant IDH1 brain tumors has generated significant efforts to understand the role of the mutated enzyme product D-2-hydroxyglutarate (D2HG), an oncometabolite, in tumorigenesis, as well as means to eliminate it. Glymphatic clearance was proposed as a pathway that could be manipulated to accelerate D2HG clearance and dictated the study design that consisted of two cohorts of mice bearing U87/mutant IDH1 intracerebral tumors who underwent two microdialysis – providing D2HG interstitial fluid concentrations - sampling periods of awake and asleep (activate glymphatic clearance) in a crossover manner. Glymphatic clearance was found not to have a significant effect on D2HG brain tumor interstitial fluid concentrations that were 126.9 ± 74.8 µM awake and 117.6 ± 98.6 µM asleep. These concentrations, although low relative to total brain tumor concentrations of 6.8 ± 3.6 mM, were considered sufficient to be transported by interstitial fluid and taken up into normal cells to cause deleterious effects. A model of D2HG CNS distribution supported this contention and was further supported by in vitro studies that showed D2HG could interfere with immune cell function. The study provides insight into the compartmental distribution of D2HG in the brain wherein the interstitial fluid serves as a dynamic pathway for D2HG to enter normal cells and contribute to tumorigenesis.